TEACHING LISTENING WITH TECHNOLOGY - Scientific advisor: Teshaboyeva Nafisa Zubaydulla qizi Student of group 101-23: Amirova Xurshida Abduaziz qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Language teachers have long used technology to practice listening. From more traditional media such as analog audio and language labs to newer, Internet-based media, technology helps provide learners with authentic and realistic experiences that add excitement to the learning process and increase their contact with the language. In this article, I will show Internet-based media Audio technology exposes students to a variety of speakers, voices, accents, situations, and rich cultural content, and it affords additional practice outside the classroom. It is easy to access and use at low or no cost. Not only does it save a teacher’s energy and voice, it offers a listener a certain degree of control over listening.